2022
DOI: 10.1111/infa.12495
|View full text |Cite
|
Sign up to set email alerts
|

Toward a dimensional model of risk and protective factors influencing children's early cognitive, social, and emotional development during the COVID‐19 pandemic

Abstract: Variation in infants' home environment is implicated in their cognitive and psycho-social development. The pandemic has intensified variations in home environments through exacerbating socioeconomic inequalities, and increasing psychological stressors for some families. This study investigates the effects of parental (predominantly maternal) mental health, enriching activities and screen use on 280 24-to 52-month-olds' executive functions, internalising and externalising problems, and pro-social behaviour; wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 128 publications
(156 reference statements)
0
9
0
1
Order By: Relevance
“…While this finding is reassuring, it should be interpreted cautiously given widespread concern that children’s mental health, social-emotional learning and communication skills, have all been negatively impacted by the unpredictability of pandemic-related disruptions to families’ lives. 29 , 30 , 31 , 32 , 33 , 34 It is possible that negative impacts on children’s development may only become clear to both families and researchers further into the future or that the types of developmental monitoring parents are engaging in are missing early concerns. Future work will need to examine how children’s development has been impacted, as children who might have been identified as needing intervention in 2020 when lockdowns were prevalent, continue to develop.…”
Section: Discussionmentioning
confidence: 99%
“…While this finding is reassuring, it should be interpreted cautiously given widespread concern that children’s mental health, social-emotional learning and communication skills, have all been negatively impacted by the unpredictability of pandemic-related disruptions to families’ lives. 29 , 30 , 31 , 32 , 33 , 34 It is possible that negative impacts on children’s development may only become clear to both families and researchers further into the future or that the types of developmental monitoring parents are engaging in are missing early concerns. Future work will need to examine how children’s development has been impacted, as children who might have been identified as needing intervention in 2020 when lockdowns were prevalent, continue to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Speculatively, this contrast may be linked to social changes as the pandemic wore on. During the first summer of the pandemic, access to ECEC may have lessened family strain (see Hendry et al, 2022) showing the association between parental mental health and child EF) and/or provided a nurturing environment for children, boosting EF. Over the extended period, these effects may have been washed out by more pervasive factors like setting quality, parental mental health rebounding, or increased social support as restrictions were loosened.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from practitioner and parental observations (e.g. DfE, 2022; Early Years Alliance, 2021; Hogg and Mayes, 2022; La Valle et al, 2022; Nicholls et al, 2020; Ofsted, 2020; Tracey et al, 2022), as well as from quantitative measures from children, their families and early years settings (Davies, Hendry et al, 2021; González et al, 2022; Green et al, 2021; Hendry et al, 2022), suggests that the lockdowns led to delays in key developmental skills. This potentially affects children’s experience of starting school, also known as school readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence indicates that childhood EFs are positively associated with access to resources and enriching interactions in the home (Hendry et al, 2022;Jasi nska et al, 2022;Kos ¸kulu-Sancar et al, 2023) and school or Early Childhood Education and Care setting (Davies et al, 2021;Kos ¸kulu-Sancar et al, 2023;Vandenbroucke et al, 2018).…”
Section: The Environment Constrains Individuals' Actualised and Upper...mentioning
confidence: 99%
“…Extensive evidence indicates that childhood EFs are positively associated with access to resources and enriching interactions in the home (Hendry et al, 2022; Jasińska et al, 2022; Koşkulu‐Sancar et al, 2023) and school or Early Childhood Education and Care setting (Davies et al, 2021; Koşkulu‐Sancar et al, 2023; Vandenbroucke et al, 2018). Sheridan, McLaughlin and others have suggested that access to resources and enriching interactions can be considered in terms of a deprivation‐enrichment scale, where at the one end children are deprived of the complex cognitive and social inputs (and perhaps moderate stressors) required for optimum cortical development, and at the other end children are exposed, with the support of responsive caregiver(s), to a range of sensory inputs, rich language and reciprocal interactions, and appropriate cognitive and physical challenge (Sheridan & McLaughlin, 2014).…”
Section: The Environment Constrains Individuals' Actualised and Upper...mentioning
confidence: 99%